Power reduction with multiple receive paths - SUTTON TODD R (2014)
Methods and apparatus for power reduction in a wireless device having multiple receive paths are described herein. A wireless device configured for any one of multiple operating modes may utilize multiple receive signal paths to improve the receive signal quality in each of the operating modes. The wireless device may be configured to dynamically reconfigure a modulation coding scheme to compensate for varying signal qualities in some modes. The wireless receiver may be configured in other operating modes where the modulation coding scheme is fixed for a duration of the operating mode. The wireless device can conserve power when it is operating in a mode supporting a constant modulation coding scheme. The wireless device can determine a signal metric value of the received signals and can selectively power down or deactivate a receive signal path based on the value of the signal metric.